How Can We Use Social Media Data Related to OA Monographs - Ozaygen, Alkim; Montgomery, Lucy; Neylon, Cameron; Wilson, Katie; Hosking, Richard; Huang, Karl (2020)
This paper reports on a study of social media events relating to 28 Open Access (OA) monographs, published between 2014 and 2015. As with citations (Cronin 1981) social media events represent the frozen footprints of the journey that monographs take as they move through digital landscapes. The study captured mentions of the study-set of monographs via Twitter, Facebook, Wikipedia and online blogs; as well as user ratings on Google Books, Amazon and Goodreads. Information relating to the ways in which the books were bookmarked and cited was captured via the online reference managing platform Mendeley. The benefits and limitations of different altmetrics approaches to capturing and analyzing this data are discussed. Practical suggestions for researchers interested in the application of Altmetrics approaches to studies of monographs are also provided.